The effect of local taxes on firm performance: Evidence from geo-referenced data - Federico Belotti; Edoardo Di Porto; Gianluca Santoni (Uppsala University, Department of Economics, 2016)
This paper studies the impact of municipal non-residential property taxation on firms' performance using a panel data of italian manufacturing firms in 2001-2010. In the spirit of Duranton et al. (2011), we use a pairwise spatial difference instrumental variable estimator which allows to tackle the endogeneity of local taxation. As well as providing robust inference to arbitrary cross-sectional dependence and serial correlation, our empirical strategy also improves on existing work by exploiting the exogenous variation in local taxes generated by the political alignment of each jurisdiction with the central government. We find that non-residential property taxation exert a negative impact on firms' employment, capital and sales to such an extent as to significantly affect total factor productivity.
urn:nbn:se:uu:diva-277268
Keywords: H22; H71; R38; 330; Local taxation; endogeneity; spatial differencing; generalized method of moments; two-way clustering